Marxismo e serviço social: um estudo sobre a incorporação da categoria “liberdade” pela tendência de ruptura com o tradicionalismo - Bezerra, Clara Angélica de Almeida Santos (2013)
This dissertation focuses the category of freedom, as understood by the critical movement to break with traditionalism social service, through theoretical contribution to Marxism. Considering the Marxian analysis of freedom, this category was for strand break social service synonymous with political emancipation, achievement of a democratic state of law. It takes as its starting point the scenario of socio-historical process of renewing the social service of the decade from 1960 to 1980 and the complex ownership of Marxism by professional category, in particular analyzes that appropriation during the erosion of the country's dictatorial regime, when the profession dialogued with various segments of society participated in the struggles and undemocratic. It explains the ontological nexus between political emancipation and human emancipation in order to pursue the Marxian conception of freedom as a historical phenomenon and dialectical, human action based on creative - work. This work in capitalist society Marx won his estranged form of wage labor, mediated by the bourgeois state that limits human freedom to political achievement of social rights, through the democratic state, forging men legally free, equal and owners to contract in market, losing its generic human dimension.